2021
DOI: 10.3390/molecules26237266
|View full text |Cite
|
Sign up to set email alerts
|

Botanical, Phytochemical, Anti-Microbial and Pharmaceutical Characteristics of Hawthorn (Crataegus monogyna Jacq.), Rosaceae

Abstract: Hawthorn (Crataegus monogyna Jacq.) is a wild edible fruit tree of the genus Crataegus, one of the most interesting genera of the Rosaceae family. This review is the first to consider, all together, the pharmaceutical, phytochemical, functional and therapeutic properties of C. monogyna based on numerous valuable secondary metabolites, including flavonoids, vitamin C, glycoside, anthocyanin, saponin, tannin and antioxidants. Previous reviews dealt with the properties of all species of the entire genera. We high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 125 publications
(171 reference statements)
0
33
0
Order By: Relevance
“…The objects of study were shoots, leaves, flowers and fruits of Crataegus rivularis Nutt.common hawthorn from the Rosaceae family, identification number according to USDA data -CRRI L48 [14]. Raw materials were harvested during various periods of the plant's vegetation in the South Ural Botanical Garden-Institute, a separate structural subdivision of the Federal State Budgetary Scientific Institution of the Ural Federal Research Center of the Russian Academy of Sciences, Ufa, the Republic of Bashkortostan, GPS coordinates: 54.727903233987,56.007758539664.…”
Section: Methodsmentioning
confidence: 99%
“…The objects of study were shoots, leaves, flowers and fruits of Crataegus rivularis Nutt.common hawthorn from the Rosaceae family, identification number according to USDA data -CRRI L48 [14]. Raw materials were harvested during various periods of the plant's vegetation in the South Ural Botanical Garden-Institute, a separate structural subdivision of the Federal State Budgetary Scientific Institution of the Ural Federal Research Center of the Russian Academy of Sciences, Ufa, the Republic of Bashkortostan, GPS coordinates: 54.727903233987,56.007758539664.…”
Section: Methodsmentioning
confidence: 99%
“…It has various pharmacological uses, such as anti-hyperlipidemia, anti-hypertension, anti-oxidation, anti-inflammation, antibacterial, anti-cancer, anti-cardiac remodeling, anti-coagulation and anti-thrombus, anti-angiotensin converting enzyme, anti-arrhythmic, and anti-cataract (Martinelli et al. 2021 ). The medicinal parts of C. scabrifolia are mainly the fruit, but its pulp, leaves, and seeds can also be used as medicine (Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in the use of these biostimulants has increased over recent decades, both in terms of improving plant growth and protecting plants from abiotic stresses [ 9 , 10 ]. The biostimulant candidate that was used in this study was an aqueous extract of Crataegus oxyacantha , a plant that contains several secondary metabolites in different areas (fruit, leaves, and flowers) and has been used for the treatment of various pharmacological activities, including antiarrhythmic activity, cardiotonic activity, and hypolipidemic activity [ 11 , 12 , 13 ]. Many studies have shown that the use of biostimulants can alleviate salt stress in plants.…”
Section: Introductionmentioning
confidence: 99%